Ten Years of the Peruvian Society of the History of Psychology - Gallegos, Walter L.Arias (2023)
This article briefly reviews the development of the history of psychology as a specialized discipline in Peru, in order to learn about the emergence, organization and productivity of the Peruvian Society of the History of Psychology (SPHP), which was founded in 2012. Previously, by way of introduction, the advances in the institutionalization of the history of psychology in Latin America and the development of the historiography of psychology in Peru are described. Seminars, journals, and books edited by the SPHP are discussed, as well as new projects and the challenges that must be faced for a greater dissemination of the history of psychology in Peru.